2013
DOI: 10.4239/wjd.v4.i5.227
|View full text |Cite
|
Sign up to set email alerts
|

Sequential elevation of autoantibodies to thyroglobulin and glutamic acid decarboxylase in type 1 diabetes

Abstract: We have previously reported the high levels of glutamic acid decarboxylase 65 autoantibodies (GAD65A) in patients with type 1 diabetes and autoimmune thyroid disease. Here we describe a 32-year-old Japanese female with a thirteen-year history of type 1 diabetes whose levels of GAD65A were elevated just after the emergence of anti-thyroid autoimmunity. At 19 years of age, she developed diabetic ketoacidosis and was diagnosed with type 1 diabetes. She had GAD65A, insulinoma-associated antigen-2 autoantibodies (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…The diagnostic sensitivity of the anti‐islet autoantibody tests we investigated tended to vary according to age at diabetes onset, with IA‐2A and ZnT8A being higher in children, and GADA being higher in adults, as reported in previous studies 6–8 . Furthermore, as previously stated, it has been reported that GADA’s persistent presence is associated with thyroid autoimmunity in patients with type 1 diabetes 9,22 and the chromosome, 3q28, in a region of strong linkage disequilibrium in the first intron of the gene, LPP 16 , which was originally identified as a susceptibility locus for celiac disease 23 and autoimmune thyroid disease 24 . Furthermore, in longitudinal studies of genetically at‐risk children followed from birth, it has been reported that the presence of multiple anti‐islet autoantibodies greatly increases the probability for type 1 diabetes 25 , and IA‐2A and ZnT8A are shown to appear later, in general, during the subclinical disease process and to herald more rapid progression to type 1 diabetes than GADA 26,27 .…”
Section: Discussionsupporting
confidence: 65%
“…The diagnostic sensitivity of the anti‐islet autoantibody tests we investigated tended to vary according to age at diabetes onset, with IA‐2A and ZnT8A being higher in children, and GADA being higher in adults, as reported in previous studies 6–8 . Furthermore, as previously stated, it has been reported that GADA’s persistent presence is associated with thyroid autoimmunity in patients with type 1 diabetes 9,22 and the chromosome, 3q28, in a region of strong linkage disequilibrium in the first intron of the gene, LPP 16 , which was originally identified as a susceptibility locus for celiac disease 23 and autoimmune thyroid disease 24 . Furthermore, in longitudinal studies of genetically at‐risk children followed from birth, it has been reported that the presence of multiple anti‐islet autoantibodies greatly increases the probability for type 1 diabetes 25 , and IA‐2A and ZnT8A are shown to appear later, in general, during the subclinical disease process and to herald more rapid progression to type 1 diabetes than GADA 26,27 .…”
Section: Discussionsupporting
confidence: 65%
“…The dynamics of humoral autoimmunity to islet autoantigens in association with anti-thyroid autoimmunity in T1DM is not clear. More frequent occurrence of positive anti-thyroid antibodies has been reported in T1DM patients as well as in LADA subjects with higher GADA titres than in those without GADA or with lower titres (15,17,27). Kawasaki et al (27) also found that persistent positivity for GADA could be associated with an increased risk of developing anti-thyroid autoimmunity in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Third, the diagnosis of autoimmune diseases in most cases was based on clinical manifestations, leaving the possibility that subclinical cases may be included in the non‐AID complicated patients. Given that high GADA levels have been detected in type 1 diabetes patients with subclinical autoimmune thyroid disease 16 , it would be beneficial to investigate the 3 Screen ICA levels in such cases.…”
Section: Discussionmentioning
confidence: 99%